IMPLEMENTASI MODEL PEMBELAJARAN KONTEKSTUAL PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN AKHLAK PESERTA DIDIK - Muhamad Irfan (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2020)
This study aims: (1) to describe the implementation of a contextual learning model in Islamic religious education learning about a sense of responsibility to students at Al Ishlah Sukadiri High School and Senior High School; (2) describe the implementation of the contextual learning model in Islamic religious education learning about the social situation to students at Al Ishlah Sukadiri High School and Senior High School; (3) describe the implementation of the contextual learning model in Islamic religious education learning about reducing tension and anxiety to students at Al Ishlah Sukadiri High School and Senior High School; This research uses a qualitative-descriptive approach. This study uses a type of field research. The design used in this study was multisite. In the use of data collection methods used are in-depth interviews, participant observation and documentation. From the results of this study, the authors conclude that: (1) The method used by the teacher in providing learning responsibility to students is by giving warnings and punishments to students who cannot be responsible for themselves with a positive punishment, namely memorizing short letters. and read istighfar. (2) The method used by the teacher in providing examples of social situations to students is by providing stories about events that are in accordance with Islamic religious education learning materials, namely empathy either directly or using learning media, in addition to providing advice and group assignments. (3) The method used by the teacher in providing learning about reducing tension and anxiety to students is by giving a comfortable impression when entering class, providing calm through contemplation by inviting students to always remember Allah.